Arbuscular-mycorrhizal fungi, rhizobia and Metarhizium anisopliae enhance P, N, Mg, K and Ca accumulatons in fields grown cowpea - Ngakou, A.; Nwaga, D.; Nebane, C.L.N.; Ntonifor, N.N.; Tamo, Manuele; Parh, I.A. (2007)
The concentrations ofP, N, K, Mg, Cain cowpea (Vigna unguiculata (L.) Walp.) roots and shoots were assessed at 45 Days After Planting (DAP) in inoculated and uninoculated plants at sowing with rhizobia and Arbuscular-Mycorrhizal Fungi (AMF). Those of harvested seeds from inoculated and uninoculated plants at sowing or sprayed and unsprayed plants at flowering with Metarhizium anisopliae were also assessed. Field trials were carried out in a complete Randomized Block Design with four treatments, in the Sudano-Sahelian (zone I), Guinea-Savannah (zone II), monomodal and bimodal hlllIlid-forest rainfall (zone IV and V) of Cameroon. The contributions of rhizobia and AMF to cowpea shoots and roots nutrients uptake at 45 DAP significantly accOlmted for up to 17% for total N, 52% for available P, 19% for Ca, 55% for Mg, 46% for K. Compared to the control, AMF+rhizobia, M. anisopliae, AMF+rhizobia and M. anisopliae significantly increased (p ~ 0.04) the N, P, Ca, Mg and K seed concentrations in zone-I (2000 and 2001), zone-II (1999), zone-IV (2004) and zone-V (1999 and 2001) at harvest. The two symbionts and M. anisopliae almost had the same influence on plant nutrient uptake within agro ecological zones. These results demonstrate the dependency of cowpea on microbial inoculants for nutrient acclUllulations in cowpea plants. However, more work still need to be camed out to investigate on the mechanisms by which M. anisopliae contributes to the increment of nutrient uptake in harvested cowpea seeds.